Effects of Gender on Self- and Supervisory Ratings - Shore, Lynn M.; Thornton, George C. (Academy of Management Journal, 1986)
This research investigated the effects of supervisors' and subordinates' genders on self- and supervisory ratings in an organizational setting. Participants were assemblers, 35 men and 35 women, and their supervisors, 16 men and 19 women. Results showed that subordinates' self-ratings were higher than their supervisors' ratings of them and that gender did not affect the relationship between self- and supervisory ratings. In prior research involving novel situations in laboratory settings, women provided lower self-ratings and higher ratings of others than men. The present study showed no gender differences in ratings on familiar tasks in a real work setting in which performance feedback was available.